Modification of Ballast Filtering Device on John Lie Training Ship to Prevent Marine Pollution - Wijaya, Haryadi; Masengi, Kawilarang Warouw Alex; Manoppo, Lefrand; Sumilat, Deiske Adeleine; Rompas, Rizald Max; Dien, Heffry Veibert; Modaso, Vivanda Octova Joulanda (PT Mattawang Mediatama Solution, 2023)
This study aims to present appropriate selection methods for evaluation, analysis, and comparison between different ballast water treatment technology systems in order to make good decisions in selecting the most optimal treatment system. This research designed a ballast water filter device on the John Lie training ship to prevent marine pollution due to species movement through the ballast water transfer process by referring to the D2 standard of the IMO Ballast Water Management Convention. During the ballasting process, ballast water contains thousands of species of marine animals and plants that are carried in ballast tanks, causing problems for the marine environment and human health. The modification of the filtration tool designed by the researcher used a 0,1 mm and 0,01 mm net tied to the ballast tank inlet pipe using a clamp on the ballast pipe of the John Lie training ship. This can fully be used during the process of filling ballast water from port seawater to enter the ballast tank through this filtration system. The results shown after passing the filter with a total plate count of 36 microorganisms indicate that the filtration system designed by the researcher can meet the D2 standard of the IMO BWM Convention Regulation.